ANALISIS PENTINGNYA PERAN ETIKA BISNIS DALAM MENCEGAH FRAUD KEUANGAN DI INDONESIA - Nurfitriyani, Nurfitriyani; Jannah, Tyara Nur Roudhatul; Alyssa Dwiprana, Mellinda Baby; Lestari, Indah Ayu (JEMBA, 2024)
ABSTRACT This study aims to analyze the effect of implementing business ethics in preventing financial fraud in Indonesia. The method used is literature review, which includes identification, assessment, analysis, and summary of relevant literature. This study focuses on cases of illegal tin mining in Indonesia involving unscrupulous businessmen and officials of large mining companies. This illegal activity is facilitated through the issuance of fake documents to give the impression of legality. Revenues from these activities are disguised as Corporate Social Responsibility (CSR) fund allocations, although they are actually used to enrich certain individuals. The impacts of these activities are significant, including severe environmental damage and hundreds of trillions of rupiah in state losses. The results of this study emphasize the importance of implementing business ethics to prevent corruption and similar illegal practices. With strong business ethics, companies can protect natural resources, support environmental sustainability and ensure public trust in transparent economic activity. These results can be used as a reference to formulate strategic policies to prevent corrupt practices in various sectors. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh penerapan etika bisnis dalam mencegah fraud keuangan di Indonesia. Metode yang digunakan adalah literatur review, yang mencakup identifikasi, penilaian, analisis, dan rangkuman literatur relevan. Studi ini berfokus pada kasus penambangan timah ilegal di Indonesia yang melibatkan oknum pengusaha dan pejabat perusahaan tambang besar. Aktivitas ilegal ini difasilitasi melalui penerbitan dokumen palsu untuk memberikan kesan legalitas. Pendapatan dari aktivitas tersebut disamarkan sebagai alokasi dana Corporate Social Responsibility (CSR), meskipun sebenarnya digunakan untuk memperkaya individu tertentu. Dampak dari aktivitas ini sangat signifikan, mencakup kerusakan lingkungan yang parah serta kerugian negara hingga ratusan triliun rupiah. Hasil penelitian ini menegaskan pentingnya penerapan etika bisnis untuk mencegah korupsi dan praktik ilegal serupa. Dengan etika bisnis yang kuat, perusahaan dapat melindungi sumber daya alam, mendukung keberlanjutan lingkungan, dan memastikan kepercayaan publik terhadap aktivitas ekonomi yang transparan. Hasil ini dapat dijadikan referensi untuk merumuskan kebijakan strategis dalam mencegah praktik korupsi di berbagai sektor.